2021
DOI: 10.1038/s41598-021-92090-6
|View full text |Cite
|
Sign up to set email alerts
|

DCBLD1 is associated with the integrin signaling pathway and has prognostic value in non-small cell lung and invasive breast carcinoma

Abstract: Germline single nucleotide polymorphisms in the promoter region of the DCBLD1 gene are associated with non-smoking cases of both non-small cell lung carcinoma (NSCLC) and human papillomavirus-negative head and neck cancer. However the clinical relevance and function of DCBLD1 remain unclear. This multicenter retrospective study was designed to evaluate the prognostic value and function of DCBLD1 in the four main solid cancers: NSCLC, invasive breast carcinoma, colorectal adenocarcinoma and prostate adenocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…It has been established that the integrin pathway will be triggered upon binding with ECM, accompanied by activation of downstream actin reorganization and MAPK signaling cascade (40). In HNSCC, the integrin pathway is involved in disease progression, tumor stem cells, and radioresistance (41,42). We also noted that GO annotations related to DCBLD1 gene included focal adhesion, cell-substrate junction, ECM organization, cell adhesion molecule binding, and other biological processes involved in ECM and cell adhesion.…”
Section: Discussionmentioning
confidence: 76%
“…It has been established that the integrin pathway will be triggered upon binding with ECM, accompanied by activation of downstream actin reorganization and MAPK signaling cascade (40). In HNSCC, the integrin pathway is involved in disease progression, tumor stem cells, and radioresistance (41,42). We also noted that GO annotations related to DCBLD1 gene included focal adhesion, cell-substrate junction, ECM organization, cell adhesion molecule binding, and other biological processes involved in ECM and cell adhesion.…”
Section: Discussionmentioning
confidence: 76%
“…A previous study showed that single nucleotide polymorphisms of promoter region of DCBLD1 was associated with head and neck cancer and lung cancer in never-smoking women (46)(47)(48)(49). Analysis of TCGA analysis demonstrated that expression of DCBLD1 was associated with worse prognosis in the patients with nonsmall cell lung cancer and invasive breast cancer (50). Notably, high expression of DCBLD1 was associated with the integrin signaling pathway (50).…”
Section: Figure 6 Effects Of Rrm2 Knockdown In Pdac Cells Validation ...mentioning
confidence: 98%
“…Analysis of TCGA analysis demonstrated that expression of DCBLD1 was associated with worse prognosis in the patients with nonsmall cell lung cancer and invasive breast cancer (50). Notably, high expression of DCBLD1 was associated with the integrin signaling pathway (50). Expression of these genes is promising as a prognostic marker for patients with PDAC.…”
Section: Figure 6 Effects Of Rrm2 Knockdown In Pdac Cells Validation ...mentioning
confidence: 99%
“…DCBLD1 is a gene encoding unknown membrane proteins, which are over-expressed in lung adenocarcinoma. Additionally, it is reported to be a prognostic factor for overall survival of non-small cell lung carcinoma (NSCLC) and breast cancer 11,12 . The expression of DCBLD1 can be inhibited by creating YY1 binding sites, which reduce the risk of lung adenocarcinoma 12 .…”
Section: Introductionmentioning
confidence: 99%